Extensive mature cystic teratoma in the pelvis of an adult male patient mimicking a prostatic abscess - Mohanad Alhumayed, MD; Joy Liau, MD, PhD (Radiology Case Reports, 2021)
Mature cystic teratomas are rare neoplasms composed of tissues from at least two of the germ layers. In the adult male pelvis, these tumors are exceptionally rare; only a small number of cases have been reported in the literature. We describe the case of a 76-year-old male with an extensive mature cystic teratoma in the rectovesical space, perineum, scrotum, and gluteal folds. This was misdiagnosed and managed as a chronic prostate abscess for six years. Few cases in the literature have reported mature cystic teratomas presenting as abscesses in male patients, and none in the male pelvis. This presentation should prompt physicians to consider the diagnosis of teratoma when managing similar cases, especially if cultures are negative and the symptoms recur despite treatment.